PREDICTING INDONESIAN FINANCIAL CRISES USING THE ARTIFICIAL NEURAL NETWORK MODEL - Syaifullah, Syaifullah (P2E-LIPI, 2013)
This study offered a method for predicting crises in Indonesia using an artificial neural network (ANN) model. The empirical findings indicated that an ANN model would have performed well in predicting crises from 1971:1 to 1995:12 (in-sample) and from 1996:1 to 1998:12 (out-of-sample), namely the Asian Financial Crisis, which hit Indonesia in 1997–1998. The empirical results indicated that financial crises can be predicted and the application of the ANN model in predicting Indonesian financial crises is promising. Thus, the government can develop an ANN model to predict recurrent financial crises and use it to provide an early warning system.